Encyclopedia Brown: the case of the exploding plumbing - Sobol, Donald J., 1924-; Shortall, Leonard W. (New York : Scholastic, 1993)
The solutions to ten mysteries solved by Leroy "Encyclopedia" Brown are given in a separate section challenging the reader to match wits with the ten-year-old mastermind of Idaville's war on crime.
Booklist
3.1
3-6
Keywords: Mystery and detective stories; Mystery fiction